Performance enhancement for the natural draft dry cooling tower under crosswind condition by optimizing the water distribution. (April 2017) - Li, Xiaoxiao; Xia, Lin; Gurgenci, Hal; Guan, Zhiqiang
Highlights: A new method has been proposed to increase the cooling tower performance in the crosswind condition. A 3D CFD model of a 20 m high NDDCT was built and the crosswind effect on this cooling tower was investigated. The water distribution method was studied on this cooling tower and the mechanism of this method was discussed. Abstract: Crosswind is a big challenge to the cooling performance of natural draft dry cooling towers (NDDCTs) and has attracted a lot of attention in previous research. This study proposed a new method to increase the performance of NDDCT under crosswind conditions by optimizing the hot water mass flow rate in the air-cooled heat exchangers. The 20 m UQ Gatton NDDCT was selected as a case study to test and validate this method. The cooling performance of this cooling tower under crosswind condition was evaluated by the 3-D CFD model. The results show that the crosswind redistributes the air flow and result in a non-uniform heat exchanger performance. By optimizing the hot water mass flow rate among the heat exchanger bundles, the cold fluids and hot fluids of the air-cooled heat exchanger can be better matched. The cooling performance of the NDDCT is increased by 18% when the crosswind speed is 4 m/s.